2012
DOI: 10.1584/jpestics.j12-03
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new acaricide, cyflumetofen

Abstract: Cy umetofen is a novel benzoylacetonitile acaricide developed by Otsuka AgriTechno Co., Ltd. It has excellent e cacy against a variety of mites that attack fruits, nuts, vegetables, tea, and ornamentals. In addition, cy umetofen exhibited long persistence e cacy against mites. e new and unique chemistry of cy umetofen provides e ectiveness against mites that have developed resistance to existing acaricides. Extensive studies have shown that cy umetofen inhibits the mitochondrial electron-transport function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 0 publications
1
40
1
1
Order By: Relevance
“…b) was shown to inhibit complex II of spider mites with a high degree of specificity, as IC 50 ranged from 3.2 to 744 nM for spider mite and housefly mitochondria respectively, and a 10–50‐fold specificity was also observed between spider mites and their phytoseiid predators . A similar specific inhibition of spider mite complex II was also reported for the active metabolite of cyflumetofen, and it was therefore suggested that the safety towards non‐target organisms of beta‐ketonitriles is mainly due to target‐site specificity …”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…b) was shown to inhibit complex II of spider mites with a high degree of specificity, as IC 50 ranged from 3.2 to 744 nM for spider mite and housefly mitochondria respectively, and a 10–50‐fold specificity was also observed between spider mites and their phytoseiid predators . A similar specific inhibition of spider mite complex II was also reported for the active metabolite of cyflumetofen, and it was therefore suggested that the safety towards non‐target organisms of beta‐ketonitriles is mainly due to target‐site specificity …”
Section: Introductionsupporting
confidence: 54%
“…The beta‐ketonitrile compounds cyflumetofen and cyenopyrafen are among the most recently developed acaricides and are in the process of being registered and commercialised for spider mite control worldwide (Fig. a and c) . They are the first compounds of a novel mode of action class of which thiapronil is the prototype compound (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the solubility of cyflumetofen in water (0.0281 mg l -1 at 20°C) (Takahashi et al 2012). Thus, owing its low water solubility, cyflumetofen was minimally transported into the internal parts of the tomato juice and seeds.…”
Section: Distribution Of Cyflumetofen In Tomato During Home Canningmentioning
confidence: 99%
“…However, a Joint FAO/WHO Meeting found that cyflumetofen is potentially carcinogenic in male rats (FAO/WHO 2006). Some researchers have reported analytical methods for cyflumetofen (Chen et al 2013;Li et al 2013) and toxicity assessments (Takahashi et al 2012), but few studies have focused on the concentration change during food processing. There are no MRLs for the related processed commodities.…”
Section: Introductionmentioning
confidence: 99%
“…) is a novel benzoyl acetonitrile acaricide developed by Otsuka AgriTechno Co., Ltd. Cyflumetofen was launched in 2007 and is now used in 15 countries around the world. Cyflumetofen shows excellent efficacy for the control of spider mites on fruit, vegetables and flowers; however, it was reported to have no effect on non‐targeted organisms including predators, aquatic organisms, honey bees and vertebrates under conditions of practical use . For example, because of this reduced environmental impact, cyflumetofen can suppress the damage caused by mites while maintaining biodiversity and safety for workers.…”
Section: Introductionmentioning
confidence: 99%